Well-Being of Infants Through Touch: The Effects of Massage on Sleep Quality and Weight Gain in the First 0-12 Months - Rayhani, Salsabila; Mochtar, Nur Mujaddidah; Djalilah, Gina Noor; Asmarani, Rewina Intan (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
The initial stage of an infant's life, from 0 to 12 months, is a critical period in their development. Growth optimization during this period depends on nutrition, emotional support, and early stimulation. Particularly, an infant's sleep quality is a key adaptive mechanism that influences their growth and well-being. This study aims to understand the impact of infant massage on the sleep quality of infants aged 0-12 months and to evaluate the influence of infant massage on weight gain in this age group. Therefore, this study conducts a systematic review of the impact of infant massage on infants aged 0-12 months, using the PubMed and Google Scholar databases from 2018 to 2023. Of 855 articles, 29 met the inclusion criteria according to PRISMA guidelines. The results show that regular infant massage, ideally 3-4 times a week for 15-30 minutes, significantly improves sleep quality and weight gain in infants aged 0-12 months. The effectiveness of infant massage is influenced by various factors such as environmental conditions, daily nutrition, massage routines, daily activities of the baby, and health conditions. This study implies that infant massage can be an important and effective intervention to support healthy infant growth and development, particularly in improving sleep quality and weight gain in infants aged 0-12 months, thereby encouraging the incorporation of infant massage as an integral part of daily baby care.